Relationship between top executive compensation and corporate governance: evidence from large Italian listed companies - Nannicini, A.; Ferraz, D. P.; Lopes, I. T. (International Journal of Disclosure and Governance, 2018)
The modernization of corporate governance aims the alignment of the interests of managers with those of companies, promoting a new discipline of internal controls and risk analysis with an enforcement of shareholder rights of information. This research investigates the impact of corporate governance variables –ownership, board of directors and remuneration committee– on executive compensation. A balanced sample of 52 Italian listed companies has been adopted to test the hypotheses, covering 55.98% and 47.13% of market capitalization in 2011 and 2015 respectively and including 669 board members. Theoretical models evidence a certain stability of compensation schemes for Italian managers over time. Findings suggest that there is a statistically significant positive effect of familiar ownership on the amount of compensation. Along with nature of ownership, the number of directors in the remuneration committee appointed by minorities assume a determinant role. With statistical significance, it affects negatively the compensation level, but, contrarily to best practices, it affects negatively the adoption of forms of incentive compensation.